2020
DOI: 10.3390/su12145579
|View full text |Cite
|
Sign up to set email alerts
|

Energy Retrofit of Social Housing with Cultural Value in Spain: Analysis of Strategies Conserving the Original Image vs. Coordinating Its Modification

Abstract: Two renovation strategies were considered and compared in this paper for the energy renovation of social housing in condo buildings built in 1945–1969, situated in residential estates that have been declared urban areas of interest. One of the strategies, named here the image conservation approach, consists of renovating the building with very efficient solutions, except for the brick-facing walls, which will only have insulation in the existing cavities. The other strategy, the image coordination appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…It is unknown to what extent the observed slowdown in the spread from March 2020 to September 2020 due to the policy's impact and not the interaction between the virus and the external environment. All renewable energy producers decreased the volume of renewable energy supply in 2020 (except China) [59][60][61][62][63][64][65]. The results expand the literature and show that various COVID-19 restrictive strategies led to a reduction in sustainable demand for renewable energy [66][67][68].…”
Section: Discussionsupporting
confidence: 52%
“…It is unknown to what extent the observed slowdown in the spread from March 2020 to September 2020 due to the policy's impact and not the interaction between the virus and the external environment. All renewable energy producers decreased the volume of renewable energy supply in 2020 (except China) [59][60][61][62][63][64][65]. The results expand the literature and show that various COVID-19 restrictive strategies led to a reduction in sustainable demand for renewable energy [66][67][68].…”
Section: Discussionsupporting
confidence: 52%
“…Energy renovation strategies of social housing are addressed in the article written by Belinda López-Mesa, Marta Monzón-Chavarrías and Almudena Espinosa-Fernández [15]. The two studied strategies are compared based on the regulation compliance, the energy use, the emissions reduction, the thermal comfort and the cost-effectiveness of the measures.…”
Section: Background and Contentsmentioning
confidence: 99%
“…López-Mesa et al found that social residential buildings erected between 1945 and 1969 with higher internal thermal mass can meet the nZEB renovation requirements more easily than those with lower thermal mass [18]. Therefore, when studying the nZEB regulation in detail, it is important to do it typology by typology.…”
Section: Introductionmentioning
confidence: 99%